(untitled) (Journal of the College of Basic Education, 2022)
Audio signal processing is one of the most important branches of digital signal processing. it has wide application in many fields, especially in communication systems and mobile phones. The aim of this study is to extract and analyze information from audio signals including the mean µ ,standard deviation σ and Signal Noise to Ratio SNR ) of the recorded audio signals as a function to the different distances. In addition to studying the histogram of these signals and comparing them with the sound signals which have been added noise to it , and improved using the median filter. The results showed high efficiency in noise removal and in maintaining the characteristics of the recorded voice signal.